Sustainable Palm Oil Management in the Tani Jaya Palm Oil Farmers Group, Rumbai Jaya Village - Mulono Apriyanto; Hermiza Mardesci; Dita Fitriani; Djono Albar Burhan; K.M.S. Novyar Satriawan Fikri (Indonesian Journal of Community Services Cel, 2025)
Background: The Indonesian government implements the Indonesia Sustainable Palm Oil (ISPO) standard to ensure environmentally responsible management of oil palm plantations. Compliance with ISPO is mandatory for both enterprises and independent smallholders involved in oil palm cultivation.Aims: A training program was established to educate these smallholders in agricultural business practices in line with ISPO principles, integrating both theoretical classroom instruction and practical field experience.Method: The training involved 45 participants, including 40 from the members of Farmer group and five independent non-member smallholders. Following this training, participants showed significant improvement in their understanding of farm business management metrics, including Equity Ratio (ER), Total Asset Turnover Ratio (TAT), and Return on Equity (ROE), among others.Results: The courses also covered essential ISPO principles such as Legal Compliance, Good Agricultural Practices, and Environmental Management. Evaluation of knowledge acquisition through written and oral assessments revealed a 95% increase in farmers' understanding of these management practices and ISPO criteria.